Advanced Photocatalytic Materials for Environmental and Energy Applications - Su, Tongming; Zhu, Xingwang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the development of modern society, environmental pollution and energy shortages have become the focus of attention worldwide. Most of the global energy supplies are generated from fossil fuel, which gives rise to environmental pollution and climate change. Photocatalysis technology, which can directly convert solar energy into high value-added fuel and chemical materials or degrade a wide range of organic pollutants into easily degradable intermediates or less toxic small molecular substances, is regarded as one of the most important ways to solve the global energy shortage and environmental pollution problem. This Special Issue focuses on advanced photocatalytic materials, including but not limited to photocatalytic materials for the treatment of indoor air, photocatalytic bacterial inactivation, photocatalytic hydrogen evolution, photocatalytic oxygen evolution, photocatalytic CO2 reduction, photocatalytic hazardous pollutant removal, the photothermal decomposition of pollutants, photoelectrochemical water splitting, etc. This Special Issue provides a platform for scientists to present their original research on "Advanced Photocatalytic Materials for Environmental and Energy Applications".